Nrf2-dependent and-independent induction of ABC transporters ABCC1, ABCC2, and ABCG2 in HepG2 cells under oxidative stress - Adachi, T.; Nakagawa, H.; Chung, I.; Hagiya, Y.; Hoshijima, K.; Noguchi, N.; Kuo, M.T.; Ishikawa, T. (2007)
Nrf2, an NF-E2-related transcription factor, plays a critical role in transcriptional upregulation of many target genes, including those for metabolizing enzymes and transporters essential for cellular defense in response to oxidative and/or electrophilic stress. In the present study, we have studied the potential involvement of Nrf2 in induction of human ABC transporter genes under oxidative stress. We created a real-time PCR primer set to quantitatively investigate the induction of human ABC transporters by a redox-active compound tert-butylhydroquinone (tBHQ) in HepG2 cells. We found that mRNA levels of ABCC1, ABCC2, ABCC3, and ABCG2 were significantly elevated in dose- and time-dependent manners. Translocation of Nrf2 into the nuclei occurred concomitantly with the induction of ABCC1 and ABCC2 as well as both heavy and light chains of gamma-glutamylcysteine synthetase (gamma-GCSh and gamma-GCSI) during tBHQ treatments. To examine the potential involvement of Nrf2 in upregulation of the ABC transporters, we treated cells with siRNA to knockdown the expression of Nrf2. Under such Nrf2-knockdown conditions, tBHQ-induced mRNA levels of ABCC2 and ABCG2 were significantly suppressed as were mRNA levels of gamma-GCSh and gamma-GCSI. Interestingly, however, the elevated mRNA level of ABCC1 was little affected by Nrf2 siRNA treatment. We also addressed the involvement of Keap1, which is a negative regulator of Nrf2 by retrieving it in the cytoplasm. When HepG2 cells were treated with Keap1-specifc siRNA, a significant increase was observed in mRNA levels of ABCC1, ABCC2, and ABCG2 as well as gamma-GCSI, suggesting that induction of ABCC2 and ABCG2 by tBHQ is mediated by the Nrf2/Keap1 system, whereas the induction of ABCC1 may involve a Keap1-dependent but Nrf2-independent mechanism.